Stimulasi Kemampuan Motorik Halus Anak Usia 5-6 Tahun Melalui Kegiatan Permainan Kolase Loose Part - Aini, Azizah; Pebrianti, Pebby; Sari, Purnama; Arani Ananda, Nur; Surya Amanda, Rizki; Sherly Utami, Winda (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Stimulating fine motor skills in children aged 5-6 years has important benefits in supporting the development of basic skills needed for daily and academic activities. This research aims to evaluate the effectiveness of the Loose Part collage game in improving children's fine motor skills. This research was conducted at Restu Bunda Kindergarten with a sample size of 10 children aged 5-6 years who were selected using purposive sampling, taking into account criteria such as age and balanced fine motor skills. The Loose Part collage game involves the use of various materials and small objects that can be arranged and arranged according to the child's imagination, to stimulate hand-eye coordination and other manipulative abilities. The method used in this research is an experimental method with a pre-test and post-test design in the control group and experimental group. Pretest research was carried out on March 15, 2024, and posttest was carried out on May 5, 2024. Research findings showed that children who were involved in the Loose Part collage game experienced a significant increase in fine motor skills compared to the control group. Therefore, the Loose Part collage game activity can be recommended as an effective method for stimulating fine motor skills in children aged 5-6 years.